Improving nutrition and physical activity behaviours of mothers with young children - Monteiro, Sarojini Maria Dos Remedios (Curtin University, 2015)
This study reported on the development, implementation and evaluation of a diet and physical activity behaviour change randomized controlled trial for mothers of young children. The six-month flexible delivery intervention was delivered via playgroups to mothers of young children. The intervention demonstrated statistically significant improvement in the intensity of vigorous, moderate and total physical activity duration. It also demonstrated a statistically significant increase in fruit and vegetable intake, and an improvement in fat and fibre eating behaviours.